Roles of dual specificity tyrosine-phosphorylation-regulated kinase 2 in nervous system development and disease - Santos-Durán, Gabriel Nicolás; Barreiro-Iglesias, Antón (Frontiers in Neuroscience, 2022)
Dual specificity tyrosine-phosphorylation-regulated kinases (DYRKs) are a group of conserved eukaryotic kinases phosphorylating tyrosine, serine, and threonine residues. The human DYRK family comprises 5 members (DYRK1A, DYRK1B, DYRK2, DYRK3, DYRK4). The different DYRKs have been implicated in neurological diseases, cancer, and virus infection. Specifically, DYRK2 has been mainly implicated in cancer progression. However, its role in healthy and pathological nervous system function has been overlooked. In this context, we review current available data on DYRK2 in the nervous system, where the available studies indicate that it has key roles in neuronal development and function. DYRK2 regulates neuronal morphogenesis (e.g. axon growth and branching) by phosphorylating cytoskeletal elements (e.g. doublecortin). Comparative data reveals that it is involved in the development of olfactory and visual systems, the spinal cord and possibly the cortex. DYRK2 also participates in processes such as olfaction, vision and, learning. However, DYRK2 could be involved in other brain functions since available expression data shows that it is expressed across the whole brain. High DYRK2 protein levels have been detected in basal ganglia and cerebellum. In adult nervous system, DYRK2 mRNA expression is highest in the cortex, hippocampus, and retina. Regarding nervous system disease, DYRK2 has been implicated in neuroblastoma, glioma, epilepsy, neuroinflammation, Alzheimer’s disease, Parkinson’s disease, spinal cord injury and virus infection. DYRK2 upregulation usually has a negative impact in cancer-related conditions and a positive impact in non-malignant conditions. Its role in axon growth makes DYRK2 as a promising target for spinal cord or brain injury and regeneration.